2016
DOI: 10.1111/jace.14445
|View full text |Cite
|
Sign up to set email alerts
|

Rare‐Earth Dopant Effects on the Structural, Energetic, and Magnetic Properties of Alumina from First Principles

Abstract: Density functional theory was used to study the effect of rare‐earth dopants on the structure, phase stability, and magnetic properties of α‐ and θ‐Al2O3. Lanthanide series rare‐earth dopants (Pr, Nd, Gd, Er, and Yb) were considered at a doping concentration of 0.83 at.%. Incorporation of rare‐earth dopants was found to increase the lattice parameters and exaggerate the local structural distortion around the dopant. The extent of local lattice distortion was correlated with the dopant ionic radii. The phase st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
5
9
0
Order By: Relevance
“…are in good agreement with other GGA calculations and only slightly overestimate the experimental values (see supplemental information for full comparison available online at stacks.iop.org/JPhysCM/30/395801/mmedia). For αalumina, the lattice vectors reported in this work are iden tical to the lattice vectors reported in [13] and within 1% of previous work, yielding a volume within 3%. Similarly, the lattice vectors reported for ϑalumina are within 1.4% of the literature, again yielding a volume within 3%.…”
Section: Energetic Stabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…are in good agreement with other GGA calculations and only slightly overestimate the experimental values (see supplemental information for full comparison available online at stacks.iop.org/JPhysCM/30/395801/mmedia). For αalumina, the lattice vectors reported in this work are iden tical to the lattice vectors reported in [13] and within 1% of previous work, yielding a volume within 3%. Similarly, the lattice vectors reported for ϑalumina are within 1.4% of the literature, again yielding a volume within 3%.…”
Section: Energetic Stabilitysupporting
confidence: 84%
“…In addition, work by Anderson et al, which included some transition metals, concluded that doping did not significantly affect the physical properties of alumina, thereby preserving its wear resistance, and ability to be used for armor applica tions [12]. Previous research examining rare earth doped alumina concluded that lanthanide doping may significantly affect the processing of alumina in the presence of a magnetic field [13]. A similar effect is expected from the 3d transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work selected these supercell dimensions to minimize interaction of the dopant with its periodic image, simulating a dilute substitutional solid solution. Larger cells change the defect formation energy by less than 0.3 meV [9,19].…”
Section: System Modelmentioning
confidence: 97%
“…Past research suggests that the total magnetic moment in the super cell may only be a partial descriptor of magnetic activity and that it is possible for dopants which are not typically considered to be good candidates for inducing magnetism to induce non-localized spin densities that are superior for texturing purposes [8,19]. It is important, therefore, to characterize not just the total magnetic moment, but also how widely distributed the magnetic moment is.…”
Section: Magnetic Moment and Spin Densitymentioning
confidence: 99%
“…The energetic favorable configuration of the vacancies is obtained by comparing the system energies with the vacancy at different lattice sites of the supercell. The perfect θ-Al 2 O 3 (the same structure as that of β-Ga 2 O 3 ) unit cell has a monoclinic structure with 20 atoms, , where O atoms can be considered approximately in the hexagonal closed stacking planes and Al atoms occupy octahedral and tetrahedral interstitial sites (as shown in Figure c). Relatively large supercells with low defect concentrations are adopted to preclude any appreciable interactions between the point defect and the supercell boundaries.…”
Section: Models and Methodsmentioning
confidence: 99%